Export of organic carbon, nutrients and metals by the mid-sized Pechora River to the Arctic Ocean - Chupakov, Artem V.; Pokrovsky, Oleg S.; Moreva, Olga Y.; Kotova, Ekaterina I.; Vorobyeva, Taissia Y.; Shirokova, Liudmila S. (Chemical Geology, 2023)
In contrast to good knowledge of export fluxes of carbon and metals from mainland to the Arctic Ocean by large Arctic Rivers, information on mid-sized rivers is limited, which prevents determining current status and foreseeing future changes in riverine export induced by climate change. Here we focused on one of the ‘middle eight’ Arctic rivers. The Pechora River (Swatershed = 322,000 km2) is the second largest European Arctic river draining through boreal forest and peatlands with partial (∼ 40%) permafrost coverage. Over 4 consecutive years (2015–2019), we measured weekly to monthly concentrations of carbon, major nutrients, and 40 major and trace elements in filtered (< 0.45 μm) river water at the terminal gauging stations for the Pechora River. The dependences between dissolved element concentration and river discharge over the full period of observation revealed 3 groups of major and trace solutes according to their seasonal behavior. Group 1 was comprised of Dissolved Inorganic Carbon (DIC), major anions (Cl, SO4), alkalis (Li, Na, K, Rb), alkaline-earth metals (Mg, Ca, Sr, Ba), elements present in the form of labile anions and neutral molecules (B, Si, Ge, Mo, Sb) and U. It demonstrated minimal concentrations during spring flooding and autumn high flow events, and maximal concentrations during winter base flow. Concentrations of these element negatively correlated with discharge. These elements primarily reflected the dominant sedimentary lithology of the Pechora catchment and were controlled by influx of underground waters hosted in carbonate rocks. Group 2 included DOC and low-mobility trivalent and tetravalent hydrolysates (Be, Al, Ga, Y, REEs, Ti, Zr, Hf, Th) and some trace metals (V, Cr, Cs, Nb). The transport of these elements to the river from the catchment likely occurred via surface and shallow subsurface waters due to leaching from organic-rich litter layer, and their concentrations positively correlated with discharge. Finally, group 3 involved major- (P, N, K) and micro-nutrients (Fe, Mn, ...